All forests are not equal: population demographics and denning behaviour of a recovering small carnivore in human modified landscapes. Issue 4 (8th October 2020) - Twining, Joshua P.; Montgomery, W. Ian; Reid, Neil; Marks, Nikki; Tosh, David G.; Scantlebury, D. Mike
Abstract : Landscapes occupied by recovering carnivore populations in Europe are highly modified by human activity. It is unclear how recovering predators will adapt and sustain populations in highly altered landscapes, with most existing research focused on large carnivores. To address this we contrast population demographics and denning behaviour of a small carnivore, the pine marten Martes martes, in a semi‐natural wooded landscape and a human‐modified landscape with limited forest cover composed of conifer plantation, using radio‐telemetry on 20 free‐ranging individuals in Northern Ireland. In the semi‐natural landscape, martens selected old growth, native forest making almost exclusive use of arboreal dens in living trees and standing deadwood. Martens persisted in the human‐modified landscape but with lower population density and recruitment, with a male‐biased sex ratio. In the human‐modified landscape martens denned in marginal habitats such as scrub, heath and property boundaries, while making use of subterranean or man‐made structures for dens in response to a lack of above ground denning opportunities. We demonstrate landscape change‐induced differences in behaviour and population structure in a recovering carnivore. The results highlight the importance of evaluating the availability of denning sites in carnivore conservation and provide valuable management considerations, key to mitigating human–wildlife conflict as carnivores continue to recover and recolonise Europe.